The Effectiveness of Code Blue Simulation on Nurses' Readiness in Cardiopulmonary Resuscitation - Anto, Ambo; Sumiyati; Peristiowati, Yuly; Susiati, Asih Luklu (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Simulation-based Code Blue training has emerged as a pedagogical approach to enhance nurses' preparedness in managing sudden cardiac arrest events. This study aims to examine the effectiveness of various Code Blue simulation models in improving Cardiopulmonary Resuscitation (CPR) competencies among nursing professionals. A systematic literature review was conducted using five recent Scopus-indexed studies that evaluated simulation-based interventions, including in situ simulations, protected Code Blue scenarios, and video-assisted debriefing. Results: The findings indicate that simulation significantly contributes to improved clinical performance, critical decision-making, and interprofessional team coordination. Conclusion: These results underscore the urgency of integrating Code Blue simulation into nursing education and training curricula to enhance professional readiness and promote patient safety..